Targeted Drug Delivery and Imaging Using Mobile Milli/Microrobots: A Promising Future Towards Theranostic Pharmaceutical Design - Vikram Singh, Ajay; Sitti, Metin (Current Pharmaceutical Design, 2016)
Miniature untethered medical robots have been receiving growing attention due to technological advances in microactuation, microsensors, and microfabrication and have significant potential to reduce the invasiveness and improve the accessibility of medical devices into unprecedented small spaces inside the human body. In this review, we discuss therapeutic and diagnostic applications of untethered medical microrobots. Wirelessly controlled milli/microrobots with integrated sensors are revolutionizing micromanipulation based medical interventions and are enabling doctors to perform minimally invasive procedures not possible before. 3D fabrication technologies enabling milli/microrobot fabrication at the single cell scale are empowering high-resolution visual imaging and in vivo manipulation capabilities. Swallowable millirobots and injectabale ocular microrobots allow the gastric ulcer imaging, and performance of vitreoretinal microsurgery at previously inaccessible ocular sites. Many invasive excision and incision based diagnostic biopsy, prostrate, and nephrolgical procedures can be performed minimally or almost noninvasively due to recent advancements in microrobotic technology. Advances in biohybrid microrobot systems are pushing microrobotic systems even smaller, using biological cells as on-board microactuators and microsensors using the chemical energy. Such microrobotic systems could be used for local targeted delivery of imaging contrast agents, drugs, genes, and mRNA, minimally invasive surgery, and cell micromanipulation in the near future.
Keywords: Microrobots